A Conclusion: The American Version of the Liberal Script, or How Exceptionalism Leads to Exceptionalism - Michael Zürn (Polarization and Deep Contestations: the Liberal Script in the United States, 2024)
How can we understand the relative strength of polarization and the authoritarian populist movement in the US? The chapter develops an endogenous explanation to this question: American exceptionalism breeds the exceptional strength and form of authoritarian populism in the US today. American exceptionalism refers here to a specific American version of the liberal script. Each liberal society has to handle a set of tensions built into the liberal script. The chapter identifies four specific features of the American version of the liberal script. It is (1) based on a strong belief in markets and the merit principle; (2) it comes with a political system full of checks and balances; (3) a multicultural or cosmopolitan tendency; and (4) it comes with a strong community orientation on the local level that proves open to truth decay. The chapter argues that these features have produced the economic, cultural, and political conditions under which authoritarian populism blossoms exceptionally well.
Keywords: 300